Looking back and moving forward: Recent advances in understanding of cardiovascular development by imaging of zebrafish. (10th April 2015) - Fukuhara, Shigetomo; Fukui, Hajime; Wakayama, Yuki; Ando, Koji; Nakajima, Hiroyuki; Mochizuki, Naoki
Abstract : Development requires cell proliferation, migration, differentiation, apoptosis, and many kinds of cell responses. Cells prepare intracellular conditions to respond to extracellular cues from neighboring cells. We have studied the development of the cardiovascular system (CVS) by visualizing morphology and signaling simultaneously using zebrafish, which express probes for both. Endodermal sheet is required for the bilateral cardiac precursor cell (CPC) migration toward the midline. Endothelial cells (ECs) proliferate specifically in the certain regions of blood vessels. Bone morphogenetic proteins (BMP) induce the remodeling of the caudal vein plexus (CVP) to form the caudal vein (CV). Our findings point to the pre‐existing neighboring cells as the cells exhibiting certain responses during the development of CVS. In this review, we introduce recent results of our research on angiogenesis and cardiogenesis by spotlighting the mechanism by which ECs and CPCs are regulated by the cells next to themselves. In addition, we discuss the unanswered questions that should be clarified in the future in the field of CVS development. Abstract : Imaging of transgenic zebrafish expressing variety of fluorescent probes enables us to understand the morphology and signal transduction simultaneously.